Features of innovative development of agriculture in the northern region (on the example of agrarian-and-industrial complex of the Komi Republic) - A. A. Yudin; A. V. Oblizov (Аграрная наука Евро-Северо-Востока, 2016)
Agriculture of the Republic of Komi is quite a contrast. It varies geographically: in terms of technological development, the volume of production and willingness to innovate. The innovative development of agriculture of the Northern region of Komi Republic is characterized by low level of innovative activity at significant scientific potential. The objective necessity of intensification of innovation processes is evidenced by the fact that for 20132015 the pace of decline in physical volume of machinery and equipment intensified; energy consumption decreased by 5%; primitive methods and technologies is dominated in agriculture; outdated varieties and breeds of cattle, imperfect forms of organization and management are used. The regulatory framework is not resolved until the end for innovation in agriculture of the Republic; there are no scientific-production association, innovation centers and agrotechnopark. Scientific-production association in the agricultural sector should be organized on the basis of Agricultural research institute of Republic of Komi. For innovative development of the Republic of Komi it is necessary to implement the strategy of innovative development of agribusiness. Firstly, used information-analytical system should be built on the basis of GIS technologies and digital maps componentwise: geomorphological, climatic, soil, farmland and derivatives thereof. Also, the set of digital maps is necessary that characterize the social conditions of agricultural production and consumption of agricultural products, infrastructure, power, process industry. This information-analytical system should provide the ability to perform scenario forecasts, and update data from different sources. Secondly, in the Strategy of economic and social development of Republic of Komi till 2020 agriculture is considered as an industry, development of which governs the economic and social welfare of the region as a whole. One of the most important tasks of development of the industry is the sharp increase in the volumes of production, which is possible through the expansion of cultivated land and parallel introduction of more advanced technologies. Thirdly, it is necessary to take into account the need for innovation of the area of main settlement and peripheral regions of the Republic of Komi.